Perception of Beauty 2017
DOI: 10.5772/intechopen.68946
|View full text |Cite
|
Sign up to set email alerts
|

Beauty and the Beast: Perception of Beauty for the Female Athlete

Abstract: This chapter is a discussion and reflection of how beauty is perceived through the lens of four different athletes over four different decades. Two basketball players, a gymnast and a skater, reflect on the language of their sport and how beauty is perceived and manipulated through language and coaching techniques. The experiences affect athletes over a lifetime, both positively and negatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Coaches can impact their athletes' view of their bodies and either inadvertently or on purpose push athletes towards negative weight control behaviors. The authors in [36] describe not only comments made to them that indicated the views and assessments of their bodies by coaches and those in power but also the objectification by others. I have worked with many young women who were encouraged to lose weight so they could be more competitive, could run faster, would look better, etc.…”
Section: Other Influences 71 Teachers Coaches and School Policiesmentioning
confidence: 99%
“…Coaches can impact their athletes' view of their bodies and either inadvertently or on purpose push athletes towards negative weight control behaviors. The authors in [36] describe not only comments made to them that indicated the views and assessments of their bodies by coaches and those in power but also the objectification by others. I have worked with many young women who were encouraged to lose weight so they could be more competitive, could run faster, would look better, etc.…”
Section: Other Influences 71 Teachers Coaches and School Policiesmentioning
confidence: 99%